Effect the Viscosity of Used Oil by Adding Chitosan Based on Shellfish and Cellulose - Fasya, Muhammad; Irawan, Doddy; Fadhilah, Raudhatul; Gunarto Gunarto (International Journal of Industrial Innovation and Mechanical Engineering, 2025)
This study explores the innovative use of chitosan from shellfish and natural cellulose as an additive to decrease the viscosity of used lubricating oils. We synthesized and applied chitosan and cellulose as adsorbents to filter impurities and enhance the rheological properties of the oil. During the experiment, different amounts of chitosan and cellulose were used, and the Ostwald method was used to measure the viscosity. As expected, adding more chitosan (20 grams) made the viscosity much better compared to mixes with cellulose. This led to a viscosity of 658.20 cP, while a 15:5 chitosan-to-cellulose ratio made the viscosity the lowest, at 513.06 cP. FTIR analyses confirmed the structural integrity of chitosan post-synthesis. Challenges in optimizing chitosan production, particularly in achieving standard deacetylation levels, were noted as potential limitations. The results suggest that using biopolymers like chitosan and cellulose together is a long-term way to improve oil recovery and reuse, lower waste, and make industrial uses better. In the future, researchers should concentrate on enhancing the manufacturing process of chitosan to enhance its adsorption capabilities, and explore alternative functional modifications that could enhance its utility in a wider range of scenarios